2018
DOI: 10.22631/ijbmph.2018.55334
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of Medicago sativa extract on the common bacterial in sinusitis infection

Abstract: Introduction: Sinusitis is a serious health hazard that is caused by inflammation of the surrounding sinus. Bacterial infection due to Streptococcus pneumonia microorganisms, Haemophilus influenza, Moraxella catarrhalis and Staphylococcus aureus is one of the factors causing sinusitis and bronchitis. Medicago sativa is known as a precious medicinal plant. The purpose of this study is to investigate the antibacterial effect of Medicago sativa extract on common bacteria in sinusitis and bronchitis. Methods: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Plants produce numerous secondary metabolites with antimicrobial properties as part of their normal growth process with the purpose to inhibit the attack of environmental pathogens; therefore, plant extracts are usually revealed with effective antibacterial properties. Previous studies have identified antibacterial and antifungal effects for: (i) black currant ( E. coli , A. niger, P. vulgaris, C. albicans —[ 64 ]); (ii) clove and thyme ( S. aureus, P. aeruginosa, E. coli, S. pyogenes, Corynebacterium spp, Salmonella spp, B. fragilis, C. albicans —[ 65 ]); (iii) blueberry ( L. monocytogenes, S. enteritidis —[ 66 ]); (iv) hibiscus ( S. typhimurium, S. aureus —[ 67 ]); (v) green tea ( S. mutans , dental bacteria—[ 68 ]); (vi) cardamom ( C. albicans, S. mutans, S. aureus, L. monocytogenes, B. cereus, S. typhimurium —[ 69 ]); (vii) alfalfa ( S. pneumonia, H. influenza, M. catarrhalis —[ 70 ]); (viii) sage ( S. mutans, S. aureus, E. coli —[ 71 ]); (ix) Echinacea ( Burkholderia cepacia complex bacteria—[ 72 ]). One mechanism through which plant extracts exhibit antimicrobial properties is the synergism between phytochemical compounds or between phytochemicals and associated antibiotics [ 73 ]; the synergistic mechanism can be explained by the association of numerous different molecules in plant extracts so that bacterial resistance through genetic mutations triggered by external stimuli is more difficult to develop [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plants produce numerous secondary metabolites with antimicrobial properties as part of their normal growth process with the purpose to inhibit the attack of environmental pathogens; therefore, plant extracts are usually revealed with effective antibacterial properties. Previous studies have identified antibacterial and antifungal effects for: (i) black currant ( E. coli , A. niger, P. vulgaris, C. albicans —[ 64 ]); (ii) clove and thyme ( S. aureus, P. aeruginosa, E. coli, S. pyogenes, Corynebacterium spp, Salmonella spp, B. fragilis, C. albicans —[ 65 ]); (iii) blueberry ( L. monocytogenes, S. enteritidis —[ 66 ]); (iv) hibiscus ( S. typhimurium, S. aureus —[ 67 ]); (v) green tea ( S. mutans , dental bacteria—[ 68 ]); (vi) cardamom ( C. albicans, S. mutans, S. aureus, L. monocytogenes, B. cereus, S. typhimurium —[ 69 ]); (vii) alfalfa ( S. pneumonia, H. influenza, M. catarrhalis —[ 70 ]); (viii) sage ( S. mutans, S. aureus, E. coli —[ 71 ]); (ix) Echinacea ( Burkholderia cepacia complex bacteria—[ 72 ]). One mechanism through which plant extracts exhibit antimicrobial properties is the synergism between phytochemical compounds or between phytochemicals and associated antibiotics [ 73 ]; the synergistic mechanism can be explained by the association of numerous different molecules in plant extracts so that bacterial resistance through genetic mutations triggered by external stimuli is more difficult to develop [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MIC of Medicago sativa root extract against Streptococcus pneumoniae, Haemophilus influenza and Moraxella catarrhalis, was 125 mg/ml. The diameter of the inhibition zone was 16 mm against Moraxella catarrhalis, 13 mm against Streptococcus pneumoniaeand 10 mm against Haemophilus influenza, while Staphylococcus aureus, showed no sensitivity to the extract [45].…”
Section: Antimicrobial Effectmentioning
confidence: 91%
“…Chegini et al [119] used maceration to obtain a biologically active compound from M. sativa. Golla et al [120] extracted peptides from seeds and used salt precipitation with a phosphate buffer against freeze-dried seeds.…”
Section: Extractionmentioning
confidence: 99%
“…The authors conclude that the antimicrobial activity of M. sativa is related to the content of medicagenic acid. Chegini et al [119] demonstrated the antibacterial effect of alfalfa root extract on the common bacteria in bronchitis and sinusitis. The results showed that the MIC value of the tested extract was 125 mg/mL against Haemophilus influenza, Streptococcus pneumoniae, and Moraxella catarrhalis.…”
Section: Gas Chromatography (Gc)mentioning
confidence: 99%